2016
DOI: 10.1055/s-0042-111512
|View full text |Cite
|
Sign up to set email alerts
|

Validierung einer Deutschen Version des Sunnybrook Facial Grading Systems

Abstract: The Sunnybrook facial grading system (SFGS) is frequently applied to evaluate facial function in patients with facial palsy, but still now there is no validated German version of this evaluation sheet. The original English version of the SFGS was translated and validated in accordance with international standards. The interrater reliability from 5 raters (speech therapy students) and the intrarater reliability from repeated ratings at 2 time points using video tapes of 18 patients with different types of facia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
(20 reference statements)
0
10
0
4
Order By: Relevance
“…In other words, the evaluations performed at different times by the same physician should be compatible with each other. It was reported that the SFGS was a reliable and valid scale in previously performed validity studies [12][13][14][15][16]. In Table 5, the inter-and intra-rater reliability results are compared with the results of the validity studies in the different languages in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the evaluations performed at different times by the same physician should be compatible with each other. It was reported that the SFGS was a reliable and valid scale in previously performed validity studies [12][13][14][15][16]. In Table 5, the inter-and intra-rater reliability results are compared with the results of the validity studies in the different languages in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Only this allowed to divide the patients into the study group (participants with central facial paresis) or the control group (participants without central facial paresis). The Sunnybrook Facial Grading System [ 52 , 53 ] is used for the standardised assessment for diagnosing facial paresis or paralysis, respectively. This measurement method is explicitly recommended [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dies erfüllt aktuell im deutschsprachigen Raum am besten das Sunnybrook Facial Grading System (Tab. 4 ; [ 10 ]). Die Facial Nerve Grading Scale 2.0 und die Electronic Clinician Graded Facial Function Scale (eFACE) sind nicht in deutscher Sprache validiert [ 11 ].…”
Section: Subjektive Und Objektive Einstufung Der Gesichtsnervenfunktionunclassified
“…Bewertet getrennt das Gesicht in Ruhe, in Bewegung und Synkinesien. Gilt als verlässliche Klassifikationsschema, und es gibt eine validierte deutsche Version [ 10 ] Facial Nerve Grading Scale 2.0 Eine Weiterentwicklung der House-Brackmann-Skala, greift Elemente des Stennert-Parese-Index auf; wird bislang wenig benutzt Electronic Clinician Graded Facial Function Scale (eFACE) Ein digitales 15-Item-Instrument mit visuellen Analogskalen; die Ergebnisse werden direkt grafisch aufgearbeitet; nichtsdestotrotz reflektiert dies wie die anderen Skalen auch die subjektive Einschätzung des Beurteilers. Eine Weiterentwicklung ist Emotrics ( https://github.com/dguari1/Emotrics ; Copyright: Diego L Guarin), eine automatische Softwarelösung, basierend auf einem maschinellen Lernverfahren …”
Section: Subjektive Und Objektive Einstufung Der Gesichtsnervenfunktionunclassified